2014
DOI: 10.1007/s00234-014-1475-3
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of hemangioblastomas from pilocytic astrocytomas using 3-T magnetic resonance perfusion-weighted imaging and MR spectroscopy

Abstract: Significantly higher rPH and lower NAA/Cr were seen in patients with hemangioblastomas when compared with PA patients, suggesting that DSC-PWI and proton MR spectroscopy are helpful in the characterization and differentiation of these two types of tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Our results of the PH parameter are in agreement with the study by She et al [14], who also showed statistically higher values of PH in HABLs than in PAs. On the other hand, the results of our PSR analysis only partially remain in agreement with the above mentioned study by She et al [14], who found both max rPSR and mean rPSR to be higher in PA.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results of the PH parameter are in agreement with the study by She et al [14], who also showed statistically higher values of PH in HABLs than in PAs. On the other hand, the results of our PSR analysis only partially remain in agreement with the above mentioned study by She et al [14], who found both max rPSR and mean rPSR to be higher in PA.…”
Section: Discussionsupporting
confidence: 93%
“…The differences in either rCBV or rPH values between HABLs and PAs may be explained easily by the distinct histological features of these two tumour types. As mentioned before, HABLs have abundant tumour vessels within lesions shown by high rCBV values and more pronounced signal drop reflected in rPH values, whereas PAs are sparsely vascularised in a wide interstitial space contributing to less pronounced perfusion curves and lower rCBV values [6,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies of brain tumor vascularization in children are rare (12)(13)(14) and have yielded varying results. Perfusion imaging studies in children are scarce and are mostly performed with T2* dynamic susceptibility contrast material-enhanced imaging (15)(16)(17)(18), which is not suitable for use in young children, as it requires high-flow injection of contrast media (19).…”
Section: Patientsmentioning
confidence: 99%
“…Only a few small studies have evaluated the advanced MR imaging features of a hemangioblastoma, 12,16,17 particularly when assessing their differentiation from a single brain metastasis. 18 The purpose of this study was to evaluate whether a hemangioblastoma can be differentiated from a single brain metastasis with DWI and DSC-PWI.…”
mentioning
confidence: 99%